Is high dose of Huperzine A really suitable for pretreatment of higher dose of soman: exists some reason for consideration? - Žďárová Karasová, Jana; Bajgar, Jiří; Novotný, Ladislav; Kuča, Kamil (Journal of Applied Biomedicine, 2009)
Huperzine A (Hup A) is a reversible AChE inhibitor that crosses the blood-brain barrier. It is presently approved for, or is in a course of clinical trials for, the treatment of Alzheimer's disease. This compound has also been successfully tested for the pretreatment of organophosphate poisoning. Organophosphate nerve agents are potent irreversible inhibitors of acetylcholinesterase in the central and also in the peripheral compartment. In this study Hup A in a higher dose (500 micro g/kg) was tested as a prophylaxis against a high, mainly centrally acting, nerve agent (soman). According to the results obtained, Hup A in this dosage was not able to protect AChE against soman in both the peripheral and central compartments. The effect of Hup A and soman was found to be additive and all animal subjects died.
Keywords: financování organizované; Animals; Statistics as Topic; Acetylcholinesterase; Rats, Wistar; statistika jako téma; Spectrophotometry; experimenty na zvířatech; Animal Experimentation; Sesquiterpenes; seskviterpeny; Financing, Organized; Male; spektrofotometrie; Soman; acetylcholinesterasa; organofosfáty; Huperzia; soman; mužské pohlaví; zvířata; Organophosphates; potkani Wistar